Ozone Therapy in the Treatment of Periodontal Disease - Dilsiz Alparslan (Journal of Dentistry And Oral Implants, 2018)
This review examines the adjunctive use of ozone therapy for periodontal disease. It summarizes proposed antimicrobial and host‑modulating effects, delivery methods, and safety considerations, and calls for standardized trials to define clinical benefit.
Keywords: Periodontal diseases